Theoretical Study on Intervention of Abdominal Vibration Therapy in Cancer-Related Depression - Qiuran LIANG; Chuanbo LIU; Kang WANG (Zhongliu Fangzhi Yanjiu, 2025)
Cancer-related depression (CRD) is a common pathological depression in the diagnosis and treatment of malignant tumors and an important factor affecting the progression and treatment of tumor diseases. Abdominal vibration therapy was developed from Professor Zang's loose vibration method. It is a set of techniques that mainly operates by vibrating the Shenque point; dredging meridians; and rubbing, pushing, and holding the abdomen. This therapy has unique advantages in the treatment of emotional diseases likely because it can stimulate the abdomen; tonify the spleen and stomach; and regulate the gut organs, the qi mechanism, and vitality. On the basis of the structure of the brain-gut axis, it regulates the inflammatory response then realizes the purpose of intervening in CRD.